The Competitive Advantage Analysis of PT Halliburton Indonesia By Using Resource Based View - Harahap, Ridho Satria (JESI (Jurnal Ekonomi Syariah Indonesia), 2021)
This research is a descriptive quantitative research embodied in a case study of PT Halliburton Indonesia. This study is aimed to analyze the company competitive advantage with the resource-based approach, through the identification towards resources and capabilities that manifest the competitive advantage and sustainable competitive advantage for the company as well. The method for data collection was conducted through the data acquired from policy maker institutions in upstream oil and gas industry and the data from related research journals, as well as distributing questionnaires and interviews to 6 subject matter experts who are the associated officials of PT Halliburton Indonesia.The research results show that there are 29 resources and 10 capabilities that influence the success of the company in the upstream oil and gas industry (strategic industry factors). Discussing in further, through the resources and capabilities appraising analysis, there are 16 resources and 8 capabilities identified as the key strengths of PT Halliburton Indonesia and become the competitive advantage for the company. Then through the VRIO test, 5 resources that become the sustainable competitive advantage for PT Halliburton Indonesia are identified. These resources are coiled tubing units, well-cementing units, packers and bridge plugs, subsurface safety valve equipment, and good corporate reputation towards clients.This research provides an overview regarding the available resources that become the sustainable competitive advantage for PT Halliburton Indonesia. Therefore, its development, maintenance, and deployment become a priority for the company. The company needs to acts to exploit those potential tangible resources in an optimal manner through a series of continuous activities of research and technology development (R&D), in similar to the intangible resource, such as a good reputation towards the client. The company needs to maintain its good reputation through the standard fulfillment of quality service in various aspects.